Coronavirus Disease 2019 and Out-of-Hospital Cardiac Arrest: No Survivors*. Issue 5 (4th October 2021) - Baert, Valentine; Beuscart, Jean-Baptiste; Recher, Morgan; Javaudin, François; Hugenschmitt, Delphine; Bony, Thomas; Revaux, François; Mansouri, Nadia; Larcher, Fanny; Chazard, Emmanuel; Hubert, Hervé
Abstract : OBJECTIVES: To describe and compare survival among patients with out-of-hospital cardiac arrest as a function of their status for coronavirus disease 2019. DESIGN: We performed an observational study of out-of-hospital cardiac arrest patients between March 2020 and December 2020. Coronavirus disease 2019 status (confirmed, suspected, or negative) was defined according to the World Health Organization's criteria. SETTING: Information on the patients and their care was extracted from the French national out-of-hospital cardiac arrest registry. The French prehospital emergency medical system has two tiers: the fire department intervenes rapidly to provide basic life support, and mobile ICUs provide advanced life support. The study data (including each patient's coronavirus disease 2019 status) were collected by 95 mobile ICUs throughout France. PATIENTS: We included 6, 624 out-of-hospital cardiac arrest patients: 127 cases with confirmed coronavirus disease 2019, 473 with suspected coronavirus disease 2019, and 6, 024 negative for coronavirus disease 2019. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: The "confirmed" and "suspected" groups of coronavirus disease 2019 patients had similar characteristics and were more likely to have suffered an out-of-hospital cardiac arrest with a respiratory cause (confirmed: 53.7%, suspected coronavirus disease 2019: 56.5%; p = 0.472) than noncoronavirus disease 2019 patients (14.0%; p < 0.001 vs confirmed coronavirus disease 2019 patients). Advanced life support was initiated for 57.5% of the confirmed coronavirus disease 2019 patients, compared with 64.5% of the suspected coronavirus disease 2019 patients ( p = 0.149) and 70.6% of the noncoronavirus disease 2019 ones ( p = 0.002). The survival rate at 30-day postout-of-hospital cardiac arrest was 0% in the confirmed coronavirus disease 2019 group, 0.9% in the suspected coronavirus disease 2019 group ( p = 0.583 vs confirmed), and 3.5% ( p = 0.023) in the noncoronavirus disease 2019 group. CONCLUSIONS: Our results highlighted a zero survival rate in out-of-hospital cardiac arrest patients with confirmed coronavirus disease 2019. This finding raises important questions with regard to the futility of resuscitation for coronavirus disease 2019 patients and the management of the associated risks.